The stress and trauma of school victimization in Ireland: A retrospective account. - MC GUCKIN, CONOR (My University, 2011)
As part of an international study examining student victimization (by both peers and educators) and posttraumatic stress disorder (PTSD) symptomatology, 154 university students completed the `Student Alienation and Trauma Scale?Revised?. This examined retrospective accounts of negative experiences in school, identified worst school experiences, and assessed whether an individual developed PTSD symptomatology. Items regarding verbal/relational aggression were reported for both the negative experiences and the worst experience. Whilst 3.1% of males and 16.3% of females reported clinically significant PTSD resulting from their worst school experience, 3.1% of males and 3.1% of females were in the `at risk? range.
PUBLISHED
Keywords: Bullying